유방 보존술 중 절제면 동결절편검사의 질 향상에 관한 연구 - 최병일; Byung-il Choi; 진수지; Su-sie Chin (Korean journal of clinical laboratory science, 2021)
유방 보존술 중 절제면 동결절편검사는 빠른 시간 내에 암세포의 유무를 판단하고 환자의 수술 범위 및 예후에 중요한 영향을 미친다. 그러나 유방조직의 특성상 많은 지방조직으로 구성되어 있고, 지방조직의 양에 따라 유방조직 동결절편검사의 정확도에 많은 영향을 미칠 수 있다. 이에 본 연구에서는 유방 보존술에서 시행하는 절제면 동결절편검사에 새로운 방법을 적용하여 기존의 동결절편검사와 비교 분석하였다. 동결절편블록의 표면을 알코올로 닦아내면 지방조직이 순간적으로 용해되면서 실질조직이 표면으로 노출될 것이라 예상하였다. 실제로 총 98례 중 기존의 동결절편검사보다 개선된 동결절편검사에서 더 높은 실질조직 비율을 얻는 경우는 37례였다. 또한 개선된 동결절편검사에서 더 높은 실질조직 비율을 얻은 37례 중 이전의 동결절편검사에서는 음성으로 진단되었으나, 개선된 동결절편검사와 영구표본조직 슬라이드에서 관상피내암으로 진단이 나온 경우는 2례였다. 비록 turn around time (TAT) 등의 한계점이 존재하지만, 본 연구 결과의 적용에 대한 논의를 계속한다면 동결 절편검사 시 조직학적 병리검사의 진단 정확성을 재고할 것이라고 사료되며, 환자 안전에도 직접적인 영향을 미칠 것이라고 판단된다. Evaluation of the resected margins of the frozen section during breast-conserving surgery can determine the presence of cancer cells in a short time and have a significant impact on the scope of surgery and the prognosis of the patient. However, breast tissue is composed of adipose tissue, which affects the accuracy of the test. In this study, a new method was applied to the resected surface of the frozen section in which wiping the surface of the frozen section block with alcohol was expected to expose the parenchyma to the surface as the adipose tissue would melt momentarily. Indeed, of the total of 98 cases, 37 cases showed a better exposure ratio of the parenchyma in the improved frozen section test than in the previous frozen section test. Of the 37 cases with increased visibility of parenchymal sections obtained by this method, two cases of ductal carcinoma in situ (DCIS) were detected. Although there are limitations such as turnaround time (TAT), the diagnostic accuracy of histopathologic examination of the frozen section may improve through this method and may have a direct impact on patient safety, and should therefore be researched further. Copyright Ⓒ 2021 The Korean Society for Clinical Laboratory Science. All rights reserved.